Lost in spacing? - Cauchi, Mark (The journal for cultural and religious theory, 2005)
A review of Catherine Malabou and Jacques Derrida, Counterpath: Travelling with Jacques Derrida, trans. David Wills, Cultural Memory in the Present, Stanford Ca.: Stanford University Press, 2004.